EVOLUTION OF ARTIFICIAL INTELLIGENCE TECHNOLOGY IN MODERN COMPUTING: AN ANALYSIS OF RECENT RESEARCH - Agus Fawait; Al-Amin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research explores the evolution of artificial intelligence (AI) technology in the context of modern computing, focusing on analysing a range of recent research. AI has undergone significant development, with key advances in machine learning, deep learning, and natural language processing that have increased its analytical and computational capacity. The review notes how AI has been widely adopted in various industries, including healthcare, automotive, finance, and manufacturing, bringing significant improvements in productivity and decision-making. However, the research also highlighted emerging challenges, such as ethical issues, data privacy, and algorithmic biases, that need serious attention. In conclusion, while AI in modern computing shows promising progress, continuous research and innovation are needed to overcome these challenges to realise AI's full potential.